Understanding Physical Literacy of Physical Education Teachers - Apriliyanto, Rizki; Sulaiman, Ahmad (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
The purpose of this study is to ascertain how well physical education teachers comprehend physical literacy. The